From Policy to Practice: An Analysis of the Implementation of Gender Mainstreaming in the City of Surabaya - Shafira Izzani Maulania; Shafina Tri Ameylia; Indah Prabawati; Firre Ann Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Gender Mainstreaming (PUG) is a development strategy aimed at achieving gender equality and justice in various aspects of social life through the integration of gender perspectives into the planning, implementation, and evaluation of development programs. Surabaya City is considered one of the regions that has successfully implemented gender mainstreaming policies, as reflected in its high Gender Empowerment Index (GEI) and various awards related to gender equality. This study uses a qualitative approach with a descriptive research type to examine the achievements of the Surabaya City Government in implementing gender mainstreaming. The data used in this study are secondary data obtained through literature studies and documentation from various sources, such as scientific journals, policy documents, government reports, and official publications related to gender mainstreaming. The collected data were then analyzed using descriptive qualitative analysis techniques. The results of the study indicate that the implementation of gender mainstreaming in Surabaya City has been carried out quite well through various gender-responsive development programs. However, the implementation still faces several obstacles, such as ineffective policy communication, limited human resources, low public understanding of gender equality, and less optimal bureaucratic coordination. Based on the analysis using George Edward III’s policy implementation theory, communication, resources, disposition, and bureaucratic structure are the main factors influencing the success of gender mainstreaming policy implementation in Surabaya City.